Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa Kelas X Sma Negeri 2 Percut Sei Tuan - Saragih, Kanya Zefanya; Hia, Yasifati (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECT OF THE REALISTIC MATHEMATICS EDUCATION (RME) APPROACH ON IMPROVING THE CONCEPTUAL UNDERSTANDING OF MATHEMATICS AMONG GRADE X STUDENTS OF SMA NEGERI 2 PERCUT SEI TUANTHE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TYPE THINK PAIR SHARE TO IMPROVE STUDENTS’ MATHEMATICAL COMMUNICATION SKILLS OF CLASSX STUDENTS OF SMA NEGERI 2 PERCUT SEI TUANStudy aims to examine the effectiveness of applying the cooperative learning model Think Pair Share in improving students’ mathematical communication skills. The research was conducted at SMA Negeri 2 Percut Sei Tuan with the subjects being 36 students of class X-F. The study employed two cycles consisting of the stages of planning, action implementation, observation, and reflection. The results showed an increase in the average score of students’ mathematical communication skills, from 30.86 in the initial test to 50.30 in cycle I, and further rising to 74.37 in cycle II. Thus, the Think Pair Share cooperative learning model proved to be effective in enhancing students’ mathematical communication skills.